Proinflammatory Microenvironment During Kingella kingae Infection Modulates Osteoclastogenesis - Pesce Viglietti, Ayelén Ivana; Sviercz, Franco Agustín; López, Cinthya Alicia Marcela; Freiberger, Rosa Nicole; Quarleri, Jorge; Delpino, María Victoria (Frontiers in Immunology, 2021)
Kingella kingae is an emerging pathogen that causes septic arthritis, osteomyelitis, and bacteremia in children from 6 to 48 months of age. The presence of bacteria within or near the bone is associated with an inflammatory process that results in osteolysis, but the underlying pathogenic mechanisms involved are largely unknown. To determine the link between K. kingae and bone loss, we have assessed whether infection per se or through the genesis of a pro-inflammatory microenvironment can promote osteoclastogenesis. For that purpose, we examined both the direct effect of K. kingae and the immune-mediated mechanism involved in K. kingae-infected macrophages induced osteoclastogenesis. Our results indicate that the osteoclastogenesis is stimulated by K. kingae infection directly and indirectly by fueling a potent pro-inflammatory response that drives macrophages to undergo functional osteoclasts via TNF-α and IL-1β induction. Such osteoclastogenic capability of K. kingae is counteracted by their outer membrane vesicles (OMV) in a concentration-dependent manner. In conclusion, this model allowed elucidating the interplay between the K. kingae and their OMVs to modulate the osteoclastogenesis from exposed macrophages, thus contributing to the modulation in joint and bone damage.